Kearifan Lokal dan Hukum Islam di Indonesia - Asni Asni (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The Islamization process through the Cultural path in the archipelago has encouraged the growth of deep-rooted Islam on the cultural bases of Indonesian society in its later development. The institutionalization stage of Islamic law also provides an area for the values of local wisdom as one of the considerations. Some of the customary law institutions already known in the community are adapted inthe positivization of Indonesian Islamic law, such as takliq talak institution, joint property, and successor heirs. Similarly, in the application of Islamic law, either through the courts or by the community, local wisdom is loaded with the value of maslahat considered in order to respond to living law in the community. In Bugis society, for example, local wisdom becomes an inseparable part of marriage based on Islamic law. Therefore, the local wisdom important to consider in the development of Islamic Law in Indonesia in the future.